2022
DOI: 10.3390/healthcare10030495
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Constraint-Induced Movement Therapy (CIMT) on Balance and Functional Mobility in the Stroke Population: A Systematic Review and Meta-Analysis

Abstract: Constraint-induced movement therapy (CIMT) is one of the most popular treatments for enhancing upper and lower extremity motor activities and participation in patients following a stroke. However, the effect of CIMT on balance is unclear and needs further clarification. The aim of this research was to estimate the effect of CIMT on balance and functional mobility in patients after stroke. After reviewing 161 studies from search engines including Google Scholar, EBSCO, PubMed, PEDro, Science Direct, Scopus, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 40 publications
1
19
0
1
Order By: Relevance
“…The limitations in the usage of the hand may further affect trunk stability [ 54 , 55 ]. The positive associations between the trunk and upper limb impairment observed in the present study suggested evaluating and minimizing the upper limb impairments and encouraging the utilization of the upper limb, which in turn can reduce the upper limb impairments and improve the trunk control, functional balance, and gait functions in late subacute stage [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 98%
“…The limitations in the usage of the hand may further affect trunk stability [ 54 , 55 ]. The positive associations between the trunk and upper limb impairment observed in the present study suggested evaluating and minimizing the upper limb impairments and encouraging the utilization of the upper limb, which in turn can reduce the upper limb impairments and improve the trunk control, functional balance, and gait functions in late subacute stage [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 98%
“…После курса комплексной МР отмечено значимое улучшение функциональной независимости по БИ. Эти результаты согласуются с предыдущими исследованиями, в которых установлено улучшение по ряду разделов БИ при использовании терапии, ограничиваю щей движение здоровой конечности (CIMT), по сравнению с обычной терапией [65].…”
Section: Discussionunclassified
“…In one included study with two CIMT groups and one active control group, the active control group was included two times in meta-analysis comparisons. For each comparison, the sample size of the active control group was divided equally ( 15 ). Positive values of Hedges' g indicate effects in favor of CIMT or otherwise in favor of the active control.…”
Section: Methodsmentioning
confidence: 99%
“…With increasing evidence that CIMT improves lower limb outcomes in stroke survivors, meta-analysis is the optimal method to explore the influence of CIMT methods on the therapeutic effects of lower limbs. Two relevant meta-analysis reviews have been published ( 15 , 16 ). These studies divided articles into different subgroups based on outcome measures; Tedla et al ( 15 ) further split articles based on outcome measures and the CIMT method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation